The values of landscape in everyday life - Monika Micheel (lo Squaderno, 2010)

(untitled)
A growing interest in landscapes and the values assigned to them can be observed in politics and planning as well as in people’s everyday life. However, discourses regarding space, spatial development and landscapes have been mainly examined from an elitist perspective. In my research, on the contrary, an everyday perspective has been adopted to develop insights into the way in which meanings and values are conferred to landscapes by the people who live in them. My approach emphasises the everyday perspective in order to deepen our understanding of the “social construction” (Berger and Luckmann 1967) of landscape.